Wesleyan Holiness and Finished Work Pentecostal Interpretations of Gog and Magog Biblical Texts - Jackson, Alicia R. (Journal of pentecostal theology, 2016)
This article surveys both Wesleyan Holiness and Finished Work Pentecostal interpretations of the Gog and Magog biblical texts (Ezekiel 38–39 and Rev. 20.7–10), examines the theology of these interpretations (observing the influence of dispensational eschatology), and evaluates how such theology affects Pentecostal mission, ethics, and politics. As dispensationalism dominated Pentecostal eschatology, readings of these texts reflected eager anticipation of the coming annihilation of God’s enemies in the Gog and Magog war or wars. Celebration of violence against those nations considered ‘doomed to divine destruction’ altered missional, ethical, and political perspectives toward these nations and peoples, contradicting the following values of early Pentecostals: (1) embrace of pacifism, (2) expectation for Christ’s imminent return, and (3) evangelistic zeal for all nations. This article demonstrates the dangers of dispensational eschatology and calls for the articulation of hopeful eschatologies that align more copacetically with Pentecostal values.